A Liquidity-Based Theory of Closed-End Funds - Cherkes, Martin; Sagi, Jacob; Stanton, Richard (Review of Financial Studies, 2009)
This paper develops a rational, liquidity-based model of closed-end funds (CEFs) that provides an economic motivation for the existence of this organizational form: They offer a means for investors to buy illiquid securities, without facing the potential costs associated with direct trading and without the externalities imposed by an open-end fund structure. Our theory predicts the patterns observed in CEF initial public offerings (IPOs) and the observed behavior of the CEF discount, which results from a trade-off between the liquidity benefits of investing in the CEF and the fees charged by the fund's managers. In particular, the model explains why IPOs occur in waves in certain sectors at a time, why funds are issued at a premium to net asset value (NAV), and why they later usually trade at a discount. We also conduct an empirical investigation, which, overall, provides more support for a liquidity-based model than for an alternative sentiment-based explanation.